The Contribution of Waste Management to Strengthening the Circular Economy and Achieving Sustainable Development in Germany (2010–2024) (Journal of Economic Additions, 2026)
This study analyzes the evolution of Germany’s waste management and its transition toward a circular economy (2010–2024). Findings reveal that recycling rates rose from 62% to over 70%, while landfilling plummeted to 1%. Economically, sector revenues reached €42 billion by 2024, with circular economy revenues totaling €108 billion and the workforce expanding to 318,000 employees. Ultimately, the German model demonstrates a successful integration of environmental sustainability and economic growth, despite persistent legislative and technological challenges.Jel Classification Codes: Q01, Q53, Q56, O44, O5
Keywords: Waste Management, Circular Economy, Recycling, Sustainable Development, Germany.